Frequency of Meningitis in Neonatal Sepsis - Anjum, Akber; Malik, Qudratullah; Nadeem, Tariq; Ullah, Naeem; Ikram, Farooq; Hussain, Murtaza (Journal of Rawalpindi Medical College, 2023)
Objective: The aim of current study was to examine the frequency of meningitis in infants having late onset sepsis (LOS). Bacterial sepsis and meningitis endure to be leading causes of illness and mortality in neonates around the world, predominantly in preterm neonates. They must be discovered and cured as soon as possible to avoid death or disability. Study Design: The Cross-Sectional method was used to conduct a study. Duration and Place of Study: The study period was July to December 2021. Data was collected from Pak Emirates Military Hospital (PEMH) NICU Rawalpindi. Material and Method: The study comprised a total of 110 individuals, both male and female. All of them were older than 3 days and had been hospitalized and diagnosed with late onset sepsis. A neonate was diagnosed with meningitis if his or her cerebrospinal fluid (CSF) had > 30 leukocytes/mm3 and any of these two: >200 mg/dl protein or 40 mg/dl glucose. Results: Out of 110 infants having LOS 38 were diagnosed with meningitis in which 21(55.2%) were male and 17(44.8%) were female. Overall mean weight of neonates was 2.38±1.72. A total of 24(63.1%) having low body weight and 22(57.8%) were premature. Meningitis was found to have a significant association with low bod weight and pre-term birth (p value<0.05). Conclusion: Meningitis was considerably high in neonates with (LOS). Low body weight and pre-term birth had significant association with meningitis having (LOS).